Determinants of Job Rotation among Administrative staff of Tamale Polytechnic, Ghana - Aboko, Akudugu; Songotua, Vitus; Ganiyu, Abudu Abdul (International Journal of Management Excellence (ISSN: 2292-1648), 2016)
This study employed descriptive survey to investigate the determinants of Job Rotation among the administrative staff at Tamale Polytechnic. A multi-stage sampling technique was employed for the study. The population was stratified into Senior Members (35), Senior Staff (45), and Junior Staff (55). Krejcie and Morgan (1970) table was used to select (32) Senior Members, (40) Senior Staff, and (48) Junior Staff respectively. Simple Random Sampling was used to select the required numbers from their respective populations. The instruments employed for the collection of data were questionnaires validated with the help of experts and pre-tested to ensure reliability. Regression analysis was used to analyse determinants of Job Rotation as assessed by Senior Members, Senior Staff, and Junior Staff computed at p < 0.05. The predictors in the construct were Age, Gender, Socio-cultural relationships, Performance, Training and Motivation of employees, while the ‘Number of Times Rotated’ in the institution formed the dependent variable. The assessment of Senior Members showed that, Performance, Training and Motivation of employees contributed largely to the explanation of the dependent variable ‘Number of Times Rotated’. This was found to be significant at .05, .04, and .03. Equally, Socio-cultural relationships, Performance, Training, and Motivation of employees contributed greatly to the explanation of the dependent variable ‘Number of Times Rotated’ and this was found to be significant at .03, .04, .04, and .03 as assessed by Senior Staff, and .01, .02, .04, and .02 as assessed by Junior Staff. To this end, the study recommends for the provision of a Job Rotation Policy that would clearly state the basis for such exercise to help increase the confidence of staff in the system.